Overcoming Barriers to Engaging Latino Older Adults in an Advance Care Planning Clinical Trial: Perspectives for Researchers and Funders. - Farro, Samantha A.; Mino, Ilian; Lum, Hillary D.; Kielty, Tatiana; Grengs, Veronica; Patel, Chandni; Haynes, Christine A. (Journal of Palliative Medicine, 2026)
Latino individuals are underrepresented in clinical trials, including studies focused on advance care planning (ACP) and palliative care. This special report describes strategies for successfully recruiting Latino older adults into the ENgaging in Advance Care Planning Talks Group Visits study, a multi-site clinical trial conducted within primary care settings. We implemented best practices from the literature to facilitate inclusion, emphasizing Spanish-speaking participants. Despite thoughtful implementation of these strategies, we confronted persistent and unique challenges in recruiting Latino and Spanish-speaking older adults, including communication channel difficulties, competing family responsibilities, financial constraints, and apprehension about research. This report outlines these barriers and details the adaptations successfully utilized to overcome them. We provide a call to action based on our experiences to promote effective inclusion of Latino older adults in ACP research and other palliative care clinical trials, highlighting the need for flexibility, culturally sensitive approaches, and sufficient resources to overcome persistent barriers.